Effect of Bifidobacterium breve M-16V supplementation on fecal bifidobacteria in preterm neonates--a randomised double blind placebo controlled trial. - Sanjay Patole (Public Library of Science (PLoS), 2014)
Background Probiotic supplementation significantly reduces the risk of necrotising enterocolitis (NEC) and all cause mortality in preterm neonates. Independent quality assessment is important before introducing routine probiotic supplementation in this cohort. Aim To assess product quality, and confirm that Bifidobacterium breve (B. breve) M-16V supplementation will increase fecal B. breve counts without adverse effects. Methods and participants Strain identity (16S rRNA gene sequencing), viability over 2 year shelf-life were confirmed, and microbial contamination of the product was ruled out. In a controlled trial preterm neonates (Gestation <33 weeks) ready to commence or on feeds for <12 hours were randomly allocated to either B. breve M-16V (3×109 cfu/day) or placebo (dextrin) supplementation until the corrected age 37 weeks. Stool samples were collected before (S1) and after 3 weeks of supplementation (S2) for studying fecal B. breve levels using quantitative PCR (Primary outcome). Secondary outcomes included total fecal bifidobacteria and NEC≥Stage II. Categorical and continuous outcomes were analysed using Chi-square and Mann-Whitney tests, and McNemar and Wilcoxon signed-rank tests for paired comparisons. Results A total of 159 neonates (Probiotic: 79, Placebo: 80) were enrolled. Maternal and neonatal demographic characteristics were comparable between the groups. The proportion of neonates with detectable B. breve increased significantly post intervention: Placebo: [S1:2/66 (3%), S2: 25/66 (38%), p<0.001] Probiotic: [S1: 29/74 (40%), S2: 67/74 (91%), p<0.001]. Median S1 B. breve counts in both groups were below detection (<4.7 log cells x g(-1)), increasing significantly in S2 for the probiotic group (log 8.6) while remaining <4.7 log in the control group (p<0.001). There were no adverse effects including probiotic sepsis and no deaths. NEC≥Stage II occurred in only 1 neonate (placebo group). Conclusion B. breve M-16V is a suitable probiotic strain for routine use in preterm neonates. Trial registration Australia New Zealand Clinical Trial Registry ACTRN 12609000374268.